Intervensi Herbal REVIVE (Rempah Vitality Versatile) Sebagai Terapi Komplementer Dalam Mengurangi Kelelahan Pekerja Wanita Perimenopause - Handayani, Puji; Lovita, Bebi; Yuniar, Dewi; Anggraini, Rizky Diah (Yayasan Jompa Research and Development, 2025)
Perimenopause is a transitional phase preceding menopause, characterized by hormonal fluctuations that frequently trigger fatigue, sleep disturbances, and reduced work performance. Women who remain active in the workforce during this stage often bear dual responsibilities at home and at work, which exacerbate their vulnerability to persistent fatigue. Complementary interventions, such as herbal-based topical therapy, may provide practical and affordable solutions. REVIVE, a topical oil formulation consisting of ginger, cinnamon, lemongrass, and virgin coconut oil, possesses anti-inflammatory, antioxidant, and relaxing properties. This study aimed to evaluate its effectiveness in reducing fatigue among perimenopausal working women. A quasi-experimental pretest–posttest control group design was applied, involving 60 female workers aged 45–55 years at Segiri Market, Samarinda, recruited through purposive sampling. Participants were randomly assigned to an intervention group (n=30) or a control group (n=30). Fatigue was measured using the Fatigue Severity Scale (FSS), and data were analyzed with paired and independent t-tests. Results demonstrated a significant reduction in fatigue scores within the intervention group, from 5.21 ± 0.81 at baseline to 3.18 ± 0.72 post-intervention (Δ = -2.03; p<0.001). In contrast, the control group showed only a minimal, non-significant change. These findings confirm that REVIVE herbal topical oil is effective in alleviating fatigue, making it a safe, accessible, and low-cost complementary therapy.This evidence highlights the potential of REVIVE as a supportive intervention in occupational health programs, contributing to women’s well-being and sustained productivity during the perimenopausal transition.